Preparation and in-vitro evaluation of Fe2O3-doped DP-bioglass in combination with 3D-printing and selective laser sintering process (3DP-SLS) for alveolar bone augmentation. Issue 9 (1st May 2021) - Chi, Chih-Ying; Chen, Ching-Yun; Huang, Jian-Yuan; Kuan, Che-Yung; Lin, Yu-Ying; Li, Chi-Han; Yang, Chun-Chen; Lin, Feng-Huei
Abstract: Severe periodontal disease can cause damage and atrophy of alveolar bone. Presently, Fe2 O3 -doped DP-bioglass (DPF-bioglass) was prepared and combined with a 3D-printing and selective laser sintering (3DP-SLS) process to prepare a porous scaffold for alveolar bone augmentation of dental implants. Addition of 2% Fe2 O3 effectively lowered the melting point and darkened the color to absorb the laser energy and increased the sintering efficiency. X-ray diffraction, optical microscopy (OM), energy dispersive spectrophotometry, and differential thermal analysis were used to characterize the crystal structure, color/darkness, morphology, qualitative chemical composition, and thermal stability, respectively, for the synthesized DPF-bioglass. After the human fetal osteoblasts (hFOB 1.19 cells) were cultured with the extraction medium, cell morphology was observed by OM. The WST-1 and lactate dehydrogenase (LDH) assays were used to evaluate the cytotoxicity of the DPF-bioglass. This bioglass was then prepared as an alveolar bone substitute (ABS) by the 3DP-SLS process and cells were cultured on the scaffold. The cell morphology was revealed by scanning electron microscopy (SEM). Cell survival rate and cells in early apoptosis were examined using live/dead and JC-1 staining, respectively. The gene expression of Runx2, type I collagen, and alkaline phosphatase (ALP) were analyzed by qPCR to check early osteogenesis, extracellular matrix secretion, and mineralization, respectively. Xylenol orange (XO) staining was used to observe the mineralization of calcium phosphate deposition. The improvements in cell attachment, proliferation, and biomineralization were further confirmed in terms of potential bone regeneration in vitro. The developed ABS was not cytotoxic to human osteoblasts in the WST-1, LDH, live/dead and JC-1 stain. The developed ABS gradually degraded and constantly released Ca +2, PO4 −3, Fe +3, and Si +4 in the physiological environment. SEM and XO staining revealed that the released ions promoted bone formation and mineralization. Osteogenesis was also enhanced, as judged by early induction of the gene expression. Graphical abstract: Schematic representation of the Fe2 O3 -doped DP-bioglass would be prepared and combined with 3D-printing sintered by the SLS process (3DP-SLS) to prepare a porous scaffold for alveolar bone augmentation in the dental implant and in-vitro of culturing human fetal osteoblast (hFOB 1.19 cells) on the scaffold to promote alveolar bone regeneration. Image 1